Immunnaja reakcija organizma tjazeloatletok na ucebno-trenirovocnych zanjatijach skorostno-silovoj napravlennosti - Rumjanceva, E. R. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The intensification of training and competitive activity in sports of the maximum achievements results in a pressure of all physiological systems of an organism. In modern sports huge on volume and intensity training loadings frequently are the reason of exhaustion of an adaptive potential of an organism and the development of a condition of disadaptation - overtraining, that has essentially an effect not only for serviceability female athletes, but also on the resistibility of their organism.